2012
DOI: 10.5667/tang.2012.0018
|View full text |Cite
|
Sign up to set email alerts
|

Homeopathic mother tincture of Conium initiates reactive oxygen species mediated DNA damage and makes HeLa cells prone to apoptosis

Abstract: Adverse side-effects and lack of scientific validation of some chemotherapeutic agents prevent the use of many traditional medicines claimed to have anti-cancer effects. Ethanolic extract of Conium maculatum has long been used in traditional and alternative systems of medicine including homeopathy for the treatment of glandular enlargements, cancerous tumours or hard lumps of testicles, prostate, ovaries, breasts and/ or uterus, particularly in the breast. However, if and how it acts still remains scientifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…After incubation with the drug, thiazolyl blue tetrazolium bromide (MTT) was added to the wells at a concentration of 10 μg/ml; plates were then incubated for 3 h at 37 °C in the dark. After incubation, colour was developed using acidic isopropanol and quercetin dose was determined at which cells’ viability reduced to 50% in 18 h ; OD was noted at 595 nm, in a microtitre plate reader (Thermo, Florida, USA).…”
Section: Methodsmentioning
confidence: 99%
“…After incubation with the drug, thiazolyl blue tetrazolium bromide (MTT) was added to the wells at a concentration of 10 μg/ml; plates were then incubated for 3 h at 37 °C in the dark. After incubation, colour was developed using acidic isopropanol and quercetin dose was determined at which cells’ viability reduced to 50% in 18 h ; OD was noted at 595 nm, in a microtitre plate reader (Thermo, Florida, USA).…”
Section: Methodsmentioning
confidence: 99%
“…C. maculatum extracts have been demonstrated in many studies to exhibit anticancer activity in multiple kinds of cancer and have the potential as a source of novel therapeutic agents. Its ethanolic extract has previously been reported for anticancer activity against cancer cell lines [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…C. maculatum is a plant used in homeopathic remedies that is utilized for the treatment of various medical conditions, including cancer. In a study conducted by Bishayee et al [ 14 ] in 2012, it was observed that an extract derived from C. maculatum , specifically the mother tincture used in homeopathy, exhibited notable anticancer properties when tested against HeLa cell lines. The mechanism underlying this anticancer activity was attributed to the initiation of reactive oxygen species (ROS)-mediated DNA damage, ultimately leading to cell death through apoptosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In homeopathy, it is used as a remedy for breast cancer and cancer of cervix uteri,[ 4 ] but its action has not yet been scientifically validated except for the report that it can inflict DNA damage by generating reactive oxygen species (ROS). [ 5 ] In this study, we contemplate to elucidate the probable mechanism of action of the drug in inducing apoptosis in the cervix cancer cell line HeLa.…”
Section: Introductionmentioning
confidence: 99%